Pendidikan Islam sebagai Sarana Pengembangan Masyarakat berdasarkan SDGS ke-4 - Aulawia Hidayati; Siti Nurhamidah Auliani; Tion Iswanto; Elsha Nurhikmah; Abdul Fadhil (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Islamic education aims to shape individuals who are faithful, possess noble character, and can make positive contributions to society. Besides transferring knowledge, Islamic education also instills spiritual, social, and intellectual values, in line with the goals of the SDGs, particularly quality and sustainable education. Its implementation involves synergy among schools, pesantren (Islamic boarding schools), and social-religious institutions. Even though it faces challenges such as resource limitations and the influences of globalization, Islamic education has significant opportunities through digital technology and government policy support. By integrating Islamic values into an adaptive and inclusive education system and strengthening collaboration among institutions, Islamic education can become a key pillar in building a civil society with global competitiveness.